Benjamin Franklin - Roop, Connie (New York : Scholastic, 2000)
A biography of the noted statesman and inventor, featuring excerpts from his letters, pamphlets, essays, scientific papers, and autobiography
Keywords: Franklin, Benjamin, 1706-1790 -- Juvenile literature; Statesmen -- United States -- Juvenile literature; Inventors -- United States -- Biography -- Juvenile literature